Intricately Regulated: A Cellular Toolbox for Fine-Tuning XBP1 Expression and Activity - Joseph W. Brewer; Andrew E. Byrd (Cells, 2012)
Stress in the endoplasmic reticulum (ER) triggers the unfolded protein response (UPR), a signaling mechanism that allows cellular adaptation to ER stress by engaging pro-adaptive transcription factors and alleviating protein folding demand. One such transcription factor, X-box binding protein (XBP1), originates from the inositol-requiring transmembrane kinase/endoribonuclease 1 (IRE1) UPR stress sensor. XBP1 up-regulates a pool of genes involved in ER protein translocation, protein folding, vesicular trafficking and ER- associated protein degradation. Recent data suggest that the regulation of XBP1 expression and transcriptional activity may be a tissue- and stress-dependent phenomenon. Moreover, the intricacies involved in “fine-tuning” XBP1 activity in various settings are now coming to light. Here, we provide an overview of recent developments in understanding the regulatory mechanisms underlying XBP1 expression and activity and discuss the significance of these new insights.